Health Education in Communities with Pulmonary TB Sufferers Prevention of Infectious Risk - Syaharuddin, Syaharuddin; Dardin, Dardin; Fardi, Fardi (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2023)
Pulmonary Tuberculosis is an infectious disease that is transmitted by Mycobacterium tuberculosis. Until now, Pulmonary Tuberculosis is still one of the main public health problems in the world, even though efforts to control Tuberculosis have been carried out in various countries. This disease, if left untreated, will cause death. The purpose of health promotion is to socialize self-prevention from TB. Lung. This community service uses a quantitative approach by using a questionnaire sheet as an instrument to find out the experiences of patients who have pulmonary TB and other communities to prevent it early. The post-test value with an average of 89% of participants answered correctly, higher than the pre-test value of 62%. The knowledge of the community at the Pertiwi Makassar city Health Center increased between 70-80% after being given counselling on self-prevention from TB Lung. The counselling used only with the lecture and demonstration method made the community understand self-prevention from TB Lung. The conclusion is that the posttest results show that the community’s knowledge is better than the posttest that has been done.